2020
DOI: 10.1016/j.str.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the PZP Domain of BRPF1 Association with Chromatin

Abstract: The assembly of human histone acetyltransferase MOZ/MORF complexes relies on the scaffolding bromodomain plant homeodomain (PHD) finger 1 (BRPF1) subunit. The PHD-zinc-knuckle-PHD module of BRPF1 (BRPF1 PZP ) has been shown to associate with the histone H3 tail and DNA; however, the molecular mechanism underlying recognition of H3 and the relationship between the histone and DNA-binding activities remain unclear. In this study, we report the crystal structure of BRPF1 PZP bound to the H3 tail and characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Phylogenetic analysis showed that PHF14 PZP stands out as an evolutionarily unique subfamily member among its paralogs (Figure 1B ). The PZP domain of BRPF1 was reported to recognize unmodified histone H3 (1–15) ( 10 , 11 ), while the AF10/AF17 subfamily PZPs were shown to recognize unmodified histone H3 (15–34) ( 14 ). The conservation and divergence of PZP family members raise an interesting question regarding the histone binding activity of PHF14 PZP .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis showed that PHF14 PZP stands out as an evolutionarily unique subfamily member among its paralogs (Figure 1B ). The PZP domain of BRPF1 was reported to recognize unmodified histone H3 (1–15) ( 10 , 11 ), while the AF10/AF17 subfamily PZPs were shown to recognize unmodified histone H3 (15–34) ( 14 ). The conservation and divergence of PZP family members raise an interesting question regarding the histone binding activity of PHF14 PZP .…”
Section: Resultsmentioning
confidence: 99%
“…The PZP domain has been identified in JADE1/2/3 (gene for apoptosis and differentiation in epithelia 1/2/3), BRPF1/2/3 (bromodomain and plant homeodomain finger containing proteins1/2/3), AF10/17 (ALL1-fused gene from chromosome 10/17), KDM4A/B/C (Lysine demethylase 4 A/B/C) and PHF14 ( 9 ). Among them, JADE PZP and BRPF PZP act as readers of unmodified histone H3K4 as well as nucleosomal DNA to regulate the acetyltransferase activity of human HBO1 (histone acetyltransferase binding to hORC1), MOZ (monocytic leukemia zinc-finger protein), and MORF (MOZ-related factor) ( 10–13 ); AF10 PZP and AF17 PZP recognize unmodified H3K27 rather than H3K27me3, and further recruit the DOT1L (histone H3K79 methyltransferase) complex to promote H3K79 methylation ( 14 ). Thus far, the histone binding activities of PHF14 and KDM4 subfamily PZP domains have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of H3-linked BRPF1 PZP was determined using materials and software listed in the key resources table . Crystallographic statistics generated for the H3-linked BRPF1 PZP structure are described in ( Klein et al., 2020 ).…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…Here, we describe biophysical and structural methods for characterization of the interactions between BRPF1 PZP , H3 tail, DNA, and the intact nucleosome. For complete details on the use and execution of this protocol, please refer to Klein et al. (2020) .…”
mentioning
confidence: 99%
See 1 more Smart Citation